A Parallel Algorithm for Geoprocessing - Saribekyan, Albert G. (Mathematical Problems of Computer Science, 2021)
Geographic information systems (GIS) play a vital role in environment-related issues, from which well-known is the calculation of vegetation indices (VI) using the satellite images. In this paper a parallel algorithm for geoprocessing of VI’s is introduced with appropriate benchmarkings, which were performed using high- performance computing (HPC) resources.